Agitation energy efficiency in gas–solid–liquid stirred vessels operating at ultra-high solids concentrations - Davoody, Meysam; Abdul Raman, Abdul Aziz; Parthasarathy, Rajarathinam (Chemical engineering research & design, 2016)
•Energy efficiency in gas–solid–liquid stirred vessels handling ultrahigh solids concentrations was investigated.•The power consumed by impeller was used most efficiently at Cv=0.2–0.3 (v/v) in the absence and presence of gas.•Effect of baffling configuration on impeller power efficiency was studied at various gas flow rates.•Increase in particle size resulted in lower energy efficiency and this phenomenon was more prominent in the absence of baffles.•Complete solids dispersion with decreased power input was obtained at just suspended condition. In this work, suspension of high-concentration slurry in the presence of gas was investigated using different baffling configurations, particle sizes, gas flow rates, and impeller types with the goal of improving the agitation energy efficiency. A term defined as power efficiency factor εjsg−1 (kg/W) was used as an indication of the amount of solid particles that could be suspended per unit of power consumed by an impeller. By varying operational parameters like solids concentration and gas flow rate, and design parameters like impeller type and baffling condition, it was found that the εjsg−1 values can be maximised by operating the tank with an optimum range of solids concentration, which is around 0.2–0.3 (v/v) for the systems studied in this work. Increase in particle size resulted in lower εjsg−1 values and this phenomenon was more prominent in unbaffled tanks. Another term, known as baffling efficiency factor, ‘Rɛ’, was used to study how baffle removal influences the energy efficiency of impellers in three-phase systems. It was observed that the absence of baffles could lead to decreased energy efficiency for axial- and mixed-flow impellers at particular operating conditions. The investigations also included the effect of baffle removal on solids dispersion, and results of this investigation indicate that it is possible to obtain complete solids dispersion with reduced power input, whilst the solids were suspended from the tank bottom.